Evaluating the dual impact of microbial activity and aged refuse layers on landfill leachate clogging: An experimental and LCA perspective - Zhaobin Li; Waifan Tang; Shulun Mak; Siukei Lam; Qingwen Li (Cleaner Engineering and Technology)
Background: Leachate-induced clogging in landfill drainage systems significantly impairs operational efficiency while posing substantial environmental risks. The complex interactions among leachate components (e.g., organic matter, heavy metals, and inorganic salts), microbial communities, and inorganic precipitates lead to clogging that reduces hydraulic conductivity. Traditional control methods often fail to address these underlying processes, necessitating a deeper understanding of clogging mechanisms and effective mitigation strategies. Significance: This study provides an in-depth analysis combining a review of existing literature and experimental insights into the role of microbial communities in clogging formation and the effectiveness of aged refuse layers as a mitigation measure.To provide a comprehensive assessment, a life cycle assessment (LCA) framework is employed to analyze the environmental impacts of various clogging control methods.This study contributes to theoretical advancements by integrating a comprehensive review of LCA frameworks in the context of landfill management, addressing a gap in current literature. The integration also provides a nuanced analysis of the environmental trade-offs and their implications for sustainable landfill practices.By integrating LCA, this research offers a dual perspective that addresses both technical challenges and environmental trade-offs, contributing to more sustainable landfill management practices. Results: Laboratory experiments demonstrated that microbial activity significantly promoted calcium carbonate precipitation, leading to reduced hydraulic conductivity in landfill drainage systems. Partially saturated aged refuse layers reduced clogging potential by up to 40% by stabilizing leachate chemistry and inhibiting biofilm formation. However, life cycle assessment (LCA) results indicate that while aged refuse layers mitigate clogging, they also increase the global warming potential (GWP) by 10% compared to conventional methods, highlighting the need to balance technical efficacy with environmental sustainability. Conclusion: This study provides critical insights into microbial contributions to landfill leachate-induced clogging and emphasizes the importance of incorporating environmental considerations into landfill management. Although aged refuse layers are effective in reducing clogging, their environmental trade-offs should be carefully evaluated. Future research should explore alternative materials and configurations to optimize both clogging control and environmental performance, promoting more sustainable landfill drainage management strategies.